2006
DOI: 10.1182/blood-2006-05-023663
|View full text |Cite
|
Sign up to set email alerts
|

Distinct memory CD4+ T-cell subsets mediate immune recognition of Epstein Barr virus nuclear antigen 1 in healthy virus carriers

Abstract: IntroductionThe human ␥-herpesvirus Epstein Barr virus (EBV) infects more than 90% of the adult population. Latent infection by EBV is associated with human cancers of epithelial and B-cell origin, including 95% of nasopharyngeal carcinoma 1 and 90% of endemic Burkitt lymphoma, and it is associated with 40% to 60% of Hodgkin lymphoma cases. 2 Although all latently infected B cells have the potential for malignant transformation, most carriers remain free of tumors due to an effective immune control of the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 38 publications
(48 reference statements)
3
62
0
1
Order By: Relevance
“…Our findings suggest that the differentiation model of Seder et al can also be extended to CD8 1 T cells, in which similarly TNF single or TNF/IL-2 double memory T cells showed the highest CCR7 expression. In line with our findings two previous studies could show that EBV-specific CCR7 1 CD4 1 and CD8 1 T cells are detectable in PB and predominately express IL-2 (Amyes et al [52] and Mallard et al [54]) and a study by Heller et al [55] showed the presence of EBNA-specific CD62L 1 T cells in PB. By sorting EBV-specific T cells based on CCR7 expression we could confirm and extend previous studies [30,52,56] showing that the CCR7 1 central memory T cells serve as reservoir for EBV-specific effector T cells (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings suggest that the differentiation model of Seder et al can also be extended to CD8 1 T cells, in which similarly TNF single or TNF/IL-2 double memory T cells showed the highest CCR7 expression. In line with our findings two previous studies could show that EBV-specific CCR7 1 CD4 1 and CD8 1 T cells are detectable in PB and predominately express IL-2 (Amyes et al [52] and Mallard et al [54]) and a study by Heller et al [55] showed the presence of EBNA-specific CD62L 1 T cells in PB. By sorting EBV-specific T cells based on CCR7 expression we could confirm and extend previous studies [30,52,56] showing that the CCR7 1 central memory T cells serve as reservoir for EBV-specific effector T cells (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…2 subset, which is consistent with published data for both CD8 + and CD4 + T cells, showing that anti-EBV cells are less differentiated than anti-CMV cells (9,45,66 (68) or during acute infection with EBV or HIV-1 (69-71). Our finding that, among the agents tested, CMV elicited the greatest responses in the CD127 2 cells, which are relatively abundant in the CCR5 + CCR2 2 subset, is consistent with previous data (58), and suggested that CMV was the virus most often (re)stimulating a systemic immune response.…”
Section: Ccr2supporting
confidence: 81%
“…Overall, based on these assays, the reported frequency of CD8 + T lymphocytes against EBV latent and lytic-stage antigens is < 2% [25,[34][35][36], and that of CD4 + T lymphocytes is typically ∼1% [2,31,32,37]. EBVspecific T cells are described as monofunctional populations secreting interferon (IFN)-γ [4,34,[38][39][40][41][42][43][44] and multifunctional cells producing tumour necrosis factor (TNF)-α, IFN-γ and interleukin (IL)-2 [12,30,31,33,37,38,45] in addition to perforin, CD107a and macrophage inflammatory protein (MIP)-1α (CCL3) [45,46]. In contrast, among individuals aged > 50 years, the results regarding anti-EBV T-cell responses in vitro are controversial.…”
Section: Introductionmentioning
confidence: 98%